The Impact of Financial Inclusion on Unemployment Rate in Developing Countries - Mehry, El-Bourainy; Ashraf, Salah; Marwa, ElSherif (International Journal of Economics and Financial Issues, 2021)
Financial inclusion has become the focus of economic policymaking worldwide. Increasing the accessibility of the weaker group of the society to formal financial services would not only serve at the individual level but will also benefit at the national level. This study aims to initially construct a new financial inclusion index for 43 developing countries based on a multidimensional approach, using Principal Component Analysis (PCA), using three dimensions; access to, usage of, and quality of financial services. Secondly, a dynamic two-step system, Generalized Method of Moments (GMM), is applied to empirically assess the impact of financial inclusion on the unemployment rate of 35 developing countries for the sample period from 2009 to 2018. The study established that financial inclusion has an impact on decreasing the unemployment rate in developing countries. The empirical findings suggest that an increase in the level of financial inclusion in developing countries decreases their unemployment rate. Moreover, the level of education, inflation rate, and economic growth have a significant negative impact on the unemployment rate. On the other hand, panel Granger Causality test was employed and indicated that there is a bi-directional causality between financial inclusion and unemployment rate. Keywords: Financial inclusion, developing countries, unemployment rate, PCA, system GMM, Granger Causaliy test. JEL Classifications: C33, E24, O11, O16 DOI: https://doi.org/10.32479/ijefi.10871